1998
DOI: 10.1007/s11661-998-0264-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation and experimental investigation of the spinodal decomposition in the β Ti-Cr binary alloy system

Abstract: The spinodal decomposition of the ␤ Ti-Cr binary alloys system is still questionable, because there are only rare experimental and thermodynamics data; moreover, simulation results for a real alloy system have not been found. Transmission electron microscopy (TEM) and quantitative computer simulations based on Khachaturyan's diffusion equation have been employed to study the microstructural evolution occurring in the metastable ␤ Ti-Cr alloys. Our study results reveal that the metastable ␤ Ti-Cr undergoes a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The oxygen content in the glove box has been reported in the ␤ phase of these alloys for Tirich compositions. [8,12,13] The metastable ␤ phase tends to was maintained below 10 ppm during all the depositions. The measured powder flow rate was 2.57 g/min, while the decompose into the solute-lean ␤ 1 and solute-rich ␤ 2 phases.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The oxygen content in the glove box has been reported in the ␤ phase of these alloys for Tirich compositions. [8,12,13] The metastable ␤ phase tends to was maintained below 10 ppm during all the depositions. The measured powder flow rate was 2.57 g/min, while the decompose into the solute-lean ␤ 1 and solute-rich ␤ 2 phases.…”
Section: Introductionmentioning
confidence: 98%
“…There have been a number of studies on the phase 760 W Nd:YAG laser, which produced near-infrared laser radiation at a wavelength of 1.064 m, was used for all the transformations occurring in Ti-Cr alloys as a function of composition and heat treatments. [8][9][10][11][12][13] A miscibility gap depositions. The energy density was in the range of 30,000 to 100,000 W/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al paper on the effect of ternary additions on decomposition of β phase in Ti-V and Ti-Mo alloys, by Miyazaki et. al on ageing effects of phase separating Ti-Cr alloys, among several others [8,13,14]. These authors concluded that α precipitated homogenously on the lean β regions and results in a finely dispersed, uniform distribution of α in the β matrix.…”
Section: Indirect Decomposition Through β Separation (β→β+β1→β+α)mentioning
confidence: 98%
“…al paper [14]on the effect of ternary additions on decomposition of β phase in Ti-V and Ti-Mo alloys, by Miyazaki et. al [13] on ageing effects of phase separating Ti-Cr alloys, among several others. Conclusions from this show that α is likely to precipitate on leaner β regions (typically 0.05µm in size).…”
Section: Stage (2): Nucleation Of α On the Intermediate Phasementioning
confidence: 99%